Internal Control and Budget Implementation in Kabale District Uganda - Eton, Marus; Caroline Murezi; Fabian, Mwosi; Benard, Patrick Ogwel (International Journal of Science and Research (IJSR), 2019)
The study saught to establish the effects of internal control systems on the budget implementation in Kabale district local government. A cross sectional study design was used and a sample of 176 respondents was chosen for the study. The study found a correlation between internal control and budget implementation (r = .568; sig. < .05) which was moderate. The study revealed that Kabale district local government had the internal controls systems mechanisms to manage risks but the actual management of risks and fraud was indeed very weak. Segregation of duties and periodical evaluation of staff were low. The policy makers at Kabale district local governments demonstrate oversight to implementation of planned activities just for the sake, otherwise, proposed projects were poorly coordinated and in some cases abandoned before completion. Though there appeared to be evidence of operating surplus budgets, the time when such budgets were passed remain in obscure to a number of concerned citizens. Internal control systems on budget implementation were indeed small and attributed majorly to management’s laxity in enforcing the existing internal controls. The study therefore recommends that Government, through the concerned organs should hold accountable the persons in charge of overseeing national and local government programs. Management at local government level should tighten and strengthen the internal control systems, sensitize local government staff at all levels to ensure adherence to existing controls to minimize fraud or corruption and reporting errors as much as possible. There is urgent need to evaluate local government staff and segregate their duties.